La organización de los servicios de documentación de las administraciones públicas en España - Peón Pérez, Jaime Luis (Revista General de Información y Documentación, 2006)
Because of the fact that the evident lack of a global reference source for the research about the documentary services and units in Spain´s Publics Administrations, their institutional framework are described since a «functional» perspective.
Keywords: Autonomous Regions; Central Government; Documentation units; Local Administration; Public Administration; Spain